Community participation and forest management dynamics in rural Cameroon. (September 2022) - Kimengsi, Jude Ndzifon; Deodatus Ngu, Ngu
Highlights: We contribute to Cameroon's on-going forest policy revision by providing renewed evidence on the role of community participation in the management of council forests. Participation in the management of council forests is skewed towards nominal participation. While the direct use of forest products significantly predicts participation in sustainable forest management, proximity to the forest does not positively predict participation. Awareness of local customs and state forest policies as an institutional determinant was more likely to shape participation than capacity building. Abstract: With more than three decades of instituting Cameroon's decentralized forest management policy, participatory approaches have been explored in her diverse forest landscapes. However, the on-going forest policy revision process begs for renewed evidence on the role of community participation in the management of council forests. We contribute, in this regard, using evidence from the western highlands, to assess the dynamics of community participation in sustainable forest management in Kedjom Ketingoh community. Using a structured questionnaire, we randomly surveyed 100 forest-dependent households in three zones constituting eleven neighborhoods of Kedjom Ketingoh community – Tiasung, Nsosoh, Fiendiang, Tualoh, Tikibeng, Tsih, Fenzhingzhing, Tomobu, Tibam, Chuketam and Sabga. We further complement the data with key informant interviews and focus group discussions. The analysis of variance (ANOVA) indicated an overall lowly ranked participation – skewed towards nominal participation. Furthermore, the binary logistic regression analysis revealed that while the direct use of forest products significantly predicts participation in sustainable forest management, proximity to the forest does not positively predict participation in sustainable forest management. Furthermore, awareness of local customs and state forest policies as an institutional determinant was more likely to shape participation than capacity building. The current forest policy revision should strategically factor in active participation, including the leveraging of robust institutions to engender meaningful participation.